Laboratory diagnosis and epidemiology of herpes simplex 1 and 2 genital infections - Glinšek, Urška (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2015)
Herpes simplex virus types 1 and 2 are the main cause of genital ulcers worldwide. Although herpes simplex virus type 2 is the major cause of genital lesions, herpes simplex virus type 1 accounts for half of new cases in developed countries. Herpes simplex virus type 2 seroprevalence rises with sexual activity from adolescence through adulthood. Slovenian data in a high-risk population shows 16% seroprevalence of HSV-2. HSV-1 and HSV-2 DNA in genital swabs was detected in 19% and 20.7%, respectively. In most cases, genital herpes is asymptomatic. Primary genital infection with herpes simplex virus types 1 and 2 can be manifested by a severe clinical picture, involving the vesicular skin and mucosal changes and ulcerative lesions of the vulva, vagina, and cervix in women and in the genital region in men. Direct methods of viral genome detection are recommended in the acute stage of primary and recurrent infections when manifest ulcers or lesions are evident. Serological testing is recommended as an aid in diagnosing genital herpes in patients with reinfection in atypical or already healed lesions. When herpes lesions are present, all sexual activities should be avoided to prevent transmission of infection. Antiviral drugs can reduce viral shedding and thus reduce the risk of sexual transmission of the virus.
Keywords: genital herpes; genitalni herpes; herpes simplex virus type 1 and 2; sexually transmitted infection; spolno prenosljiva okužba; virus herpes simpleks 1 in 2